2009
DOI: 10.1038/jcbfm.2009.71
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Choroid Plexus in Neutrophil Invasion after Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) frequently results in neuroinflammation, which includes the invasion of neutrophils. After TBI, neutrophils infiltrate the choroid plexus (CP), a site of the blood-cerebrospinal fluid (CSF) barrier (BCSFB), and accumulate in the CSF space near the injury, from where these inflammatory cells may migrate to brain parenchyma. We have hypothesized that the CP functions as an entry point for neutrophils to invade the injured brain. Using the controlled cortical impact model of TBI in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(137 citation statements)
references
References 37 publications
7
130
0
Order By: Relevance
“…The type I IL-1 receptor has previously been identified by in situ hybridization to be expressed in the CP (Ericsson et al, 1995), and we have confirmed its expression on epithelial monolayers (Szmydynger-Chodobska et al, 2009).…”
Section: Polarity Of Ccl2 Secretion By Choroidal Epitheliumsupporting
confidence: 82%
See 3 more Smart Citations
“…The type I IL-1 receptor has previously been identified by in situ hybridization to be expressed in the CP (Ericsson et al, 1995), and we have confirmed its expression on epithelial monolayers (Szmydynger-Chodobska et al, 2009).…”
Section: Polarity Of Ccl2 Secretion By Choroidal Epitheliumsupporting
confidence: 82%
“…Similar to the movement of neutrophils (Szmydynger-Chodobska et al, 2009), the migration of monocytes across the BCSFB appeared to involve the paracellular pathway. The movement of monocytes along the paracellular pathway was frequently associated with the widening of space between invading inflammatory cells and the adjacent epithelial cells (see Figures 4H and 4I), a phenomenon not observed for migrating neutrophils (Szmydynger-Chodobska et al, 2009). Interestingly, monocytes were sometimes found to invade the ipsilateral CP in tandem with neutrophils (see Figure 4J).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…5c). Indeed, the choroid plexus transcriptome, proteome, and secretome are dynamic and rapidly change in response to external cues, such as inflammation [89,155]. Choroid plexus epithelial cells have many villi, providing a large surface area for detection of signals in the CSF.…”
Section: Sensor and Modulator Of Physiological States In The Adultmentioning
confidence: 99%